Comparing intraregional trends of demographic development in the Russian Near North (on the example of Arkhangelsk, Vologda, and Kostroma Oblasts) - Mokrensky, Denis N. (Population and Economics, 2022)
The article compares intraregional trends in demographic development of the old-developed territories of the Russian Near North: Arkhangelsk, Vologda, and Kostroma Oblasts. The author identifies trends in the fertility, mortality, and migration in 2011—2019 basing on the statistical indicators characterizing the demographic situation in municipal entities and urban districts of the old-developed areas in these regions. A comparative analysis of the demographic dynamic in the three regions confirmed the well-known conclusions about depopulation, urbanization, and migration loss in most municipalities. Steady depopulation was observed in medium-sized and small cities, including in municipal centers, where the inflow of population from the nearest periphery is decreasing. The further away from Moscow the region is, the higher the growth rate of the urban population and the rate of decline in the rural population.